Agrarian Law Review Of Planting Area Expansion In Support Of The Food Self Sufficiency Program - Sulthoni Ajie Sahidin; Atik Winanti; Irwan Joesoef (Journal of Law Perspectives Review, 2026)
This study aims to analyze the regulation of agrarian law in supporting the program to expand planting areas as an effort to realize national food self-sufficiency, identify juridical obstacles in its implementation, and formulate a more effective strengthening of agrarian law policies. The research uses normative legal research methods with a statute approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed qualitatively using prescriptive analysis methods. The results of the study show that the framework of Indonesian agrarian law, which is based on the Constitution of the Republic of Indonesia in 1945, Law Number 5 of 1960 concerning the Basic Regulations on Agrarian Principles, and Law Number 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land, has provided an adequate legal basis for the implementation of the planting area expansion program. However, its implementation still faces various obstacles, including the conversion of agricultural land, land conflicts, the suboptimal use of abandoned land, weak institutional coordination, and disharmony of regulations across sectors. Strengthening agrarian law policies through agricultural land protection, optimization of agrarian reform, improving the quality of land administration, harmonizing regulations, and consistent law enforcement are strategic steps to create legal certainty and support the success of food self-sufficiency programs in a sustainable manner.